(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The paper critically looked at the various challenges militating against development of inclusion education in Nigeria. The paper is a position paper. Secondary data were used in the paper. The secondary data were collected from print and online publications. The study disclosed that inadequate funding and resource constraints, poor teacher preparation and professional development, inadequate infrastructure and learning environment, insecurity programme, negative societal and cultural attitudes, weak policy implementation and institutional support, technological and digital barriers, curriculum inflexibility and assessment issues and corruption are some of the challenges facing inclusive education in Nigeria. Based on these findings, the paper recommends that increment in funding and ensuring equitable resource allocation, enhance teacher training and professional development, improve educational infrastructure and learning environment, strengthen security in educational institutions, promote positive societal and cultural attitudes toward inclusion, ensure effective policy implementation and institutional support, integrate technology and digital inclusion in schools, revise curriculum and reform assessment practices, promote transparency and combat corruption in education management and foster multi-sectoral and community collaboration.